Progress and prospects of nanocomposite hydrogels in bone tissue engineering. Issue 1 (10th May 2022) - Du, Chengcheng; Huang, Wei
Abstract: Hydrogels are hydrophilic polymers with high flexibility and elasticity, and are widely used in the field of bone tissue engineering. However, their low toughness and insufficient mechanical strength have limited their applications. Nanocomposite hydrogels are flexible and porous as well as possess excellent biocompatibility and mechanical strength, thus exhibiting a significant potential to be used in the field of bone tissue engineering. Nanocomposite hydrogels are synthesized by chemically or physically crosslinking nanomaterials and hydrogels, and their physical, chemical, and biological properties can be enhanced by changing the properties and compositions of the nanomaterials. Both nanomaterials and hydrogel polymers can be customized, and therefore, nanocomposite hydrogels can be developed for bone repair under different conditions. In this review, we first introduce the synthesis methods and properties of nanocomposite hydrogels, and then summarize the applications and progress of nanocomposite hydrogels in bone tissue engineering. Graphical Abstract: UF0001 Nanocomposite hydrogels are used in bone tissue engineering. Adapted from Huang et al. (2019) [121 ]